Bioactivity of Achillea millefolium and Urtica dioica extracts in vitro - Mannila, Enni (My University, 2020)
Achillea millefolium (AM, English: Yarrow) and Urtica dioica (UD, English: Nettle) are common plants that are used traditionally as medicinal herbs, and nowadays, as food supplements (AM) or as food (UD). In this work, the extraction processes and the specific bioactivities of the extracts were investigated. The extraction process was optimized for each species with the response surface method by measuring total carotenoid, chlorophyll and phenolic compound (TPC) contents and two antioxidant capacity tests. Optimal extraction parameters were a one-hour extraction in 70 % ethanol at +45 °C for AM, and at +49 °C for UD. Bioactive effects were tested against potential food-pathogenic and beneficial strains of bacteria and murine norovirus. Aqueous version and commercial antimicrobial blend were used as a comparison. In addition, the conventional extraction (CE) was compared with pulsed electric field (PEF) assisted extraction with 50 % ethanol with the same tests as in optimization and antibacterial effects. Effects on bacterial growth depended on the bacterial strain, the solvent and the extraction method and time. In general, the ethanolic extracts were more antimicrobial than the aqueous extracts, and AM was more antibacterial than UD. In certain cases, PEF was more effective than CE, but in some cases the time was more important factor. The extracts were more effective on Gram-positive than Gram-negative bacteria, and there were no remarkable effects on beneficial bacteria. There was a positive correlation between TPC, antioxidant activity and antibacterial effects with L. innocua. The obtained results form a basis for future studies on the effects of these plants on gut microbiota and their bioactive effects in vivo.

Achillea millefolium (AM, suom. Siankärsämö) ja Urtica dioica (UD, suom. Nokkonen) ovat yleisiä kasveja, joita on käytetty lääkeyrtteinä ja nykyään ravintolisinä (AM) ja elintarvikkeena (UD). Tässä erikoistyössä tutkittiin näiden kasvien uuttoprosesseja ja uutteiden bioaktiivisuuksia. Uuttoprosessi optimoitiin kummallekin kasville vastepintamenetelmällä määrittämällä uutteen kokonaiskarotenoidi, -klorofylli ja fenolisten yhdisteiden määrät sekä antioksidanttiaktiivisuus kahdella eri menetelmällä. Optimoidut uutto-olosuhteet olivat tunnin uutto 70-prosenttisella etanolilla +45 °C:n lämpötilassa AM:lle ja +47 °C:n UD:lle. Optimoitujen uutteiden bioaktiivisia ominaisuuksia testattiin mahdollisten elintarvikepatogeenien ja hyödyllisten bakteerien kasvuun sekä hiiren norovirukseen. Vertailuna käytettiin kasvien vesiuutteita sekä bakteerikokeissa kaupallista antimikrobista seosta. Lisäksi perinteistä (CE) ja pulssitetulla sähkökentällä (PEF) avustettua uuttoa 50-prosenttisella etanolilla vertailtiin käyttämällä samoja määrityksiä kuin optimoinnissa sekä testaamalla vaikutuksia bakteerien kasvuun. Vaikutus bakteerien kasvuun riippui bakteerista, käytetystä liuottimesta, uuttotavasta ja -ajasta. Optimoidut etanoliuutteet olivat tehokkaampia kuin vesiuutteet ja AM esti bakteerien kasvua paremmin kuin UD. PEF oli osittain tehokkaampi kuin CE, mutta joissain tapauksissa uuttoajalla oli enemmän merkitystä. Uutteet olivat tehokkaampia testattuihin grampositiivisiin kuin gramnegatiivisiin bakteereihin ja hyödyllisten bakteerien kasvuun niillä ei huomattu merkittävää vaikutusta. Fenolisten yhdisteiden määrällä ja antioksidanttiaktiivisuudella oli positiivinen yhteys antibakteerisiin ominaisuuksiin L. innocua -bakteerille. Saadut tulokset toimivat pohjana tuleville tutkimuksille näiden kasvien vaikutuksista suoliston mikrobistoon ja bioaktiivisiin ominaisuuksiin in vivo.
Keywords: Achillea millefolium, Urtica dioica, bioactivity, antibacterial effects, extraction optimization